Coastal Community Empowerment Recovery of cockle shell waste into eco-friendly artificial reefs in Mutiara Beach Trenggalek Indonesia - Mirna Apriani; Anggara Trisna Nugraha; Agung Prasetyo Utomo; Luqman Cahyono; Achmad Fauzi; Tri Utami; Arum Putri Nur Romadhoni; Diego Ilham Yoga Adna; Fauzan Kholistya Hanif (Frontiers in Community Service and Empowerment, 2022)
The community empowerment activity is conducted in the form of training of trainers (TOT) and mentoring for the community of Mutiara Beach, Trenggalek, East Java. Trenggalek Regency has regional dominance of mountains and hills is located in the southern part of East Java Province. The improvement of facilities at Mutiara Beach is increasingly being improved in line with one hundred tourist programs. The marine environment must be maintained to remain sustainable and can support tourism, one of which is by maintaining conservation of coral reefs. The existing condition of coral reef was stressed and needs to be restored. Artificial reefs can also be made of concrete mixed with cockle shells that have not been used so far. The concept of processing cockle shell waste emerged by reusing it as a mixture of material and as a roughage material for artificial reefs. The purpose of community empowerment is to give training for local community as a trainer for sustainability transfer knowledge. Method to achieve the goal using socialization, giving brief explanation and directly hands-on practice. Artificial reef has been manufactured from TOT, analyzed to compare with criteria design in order to decide the success of TOT has been achieved. TOT resulting trainers from Pokmaswas as a leader to produce artificial reef with local community. The trainers were success to manage local community with resulting seven artificial reefs with their creativity. Local community was able to identify alternative material in order to change cockle shell with coral flakes carried by tide sea.